Keefektifan Pemakaian Modul dalam Pembelajaran Reading Comprehension pada Persiapan Tes TOEIC di IKIP Budi Utomo Malang - Maya Rizki Amalyasari (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2016)
In International work environment, TOEIC test (Test of English for International Communication) is one of the factors or qualifications dealing with International communication. The result of TOEIC test becomes the reference on how far someone has the ability in mastering English both in Reading Skill and Listening Skill. Whenever someone is able to reach the standard score of TOEIC test, it can be said that he or she is able to communicate both written and orally. Moreover, he or she is able to communicate in English as well. In this research, the researcher focused on the ability of the lecturers of IKIP Budi Utomo Malang in mastering English, especially Reading Comprehension in TOEIC test. Focus on Reading Comprehension Skill was chosen since many lecturers of IKIP Budi Utomo Malang did not reach the standard score of TOEIC test, thus, they did not pass the TOEIC test. Dealing with mastering of Reading Comprehension skill, the researcher implemented Module which contains of Reading Comprehension knowledge and English Grammar knowledge. This Module was then implemented to help the lecturers of IKIP Budi Utomo Malang to understand those materials easily. In this research, the researcher implemented pre-experimental research by giving pre-test and post-test to the lecturers of IKIP Budi Utomo Malang. This pre-test was used to know exactly the ability of the lecturers in mastering Reading Comprehension before they had been given treatment. Then, the post test was used to measure the effectiveness of the implementation of Module in giving understanding and raising lecturers’ understanding of Reading Comprehension skill. The implementation of Module was able to raise the lecturers’ understanding of Reading Comprehension in TOEIC test, thus, they could reach the standard score in TOEIC test.